Taxonomy, distribution, and conservation status of a rare arboreal lizard, Bronchocela hayeki (Müller, 1928) (Reptilia: Agamidae) from northern Sumatra, Indonesia - Amarasinghe, A.a. Thasun; Kamsi, Mistar; Riyanto, Awal; Putra, Chairunas A.; Hallermann, Jakob; Andayani, Noviar; Abinawanto, A.; Supriatna, Jatna (Zootaxa, 2022)
Bronchocela hayeki (Müller, 1928) is one of the rarest species of the genus, known only from a handful of museum specimens from five locations in North Sumatra, and often confused with its similar congener, B. cristatella, which occurs widely throughout the Indonesian Archipelago and Peninsular Malaysia. Here, we examined the morphology of B. hayeki based on museum specimens, and redescribe the species based on a freshly collected series near the type locality, as the condition of its neotype is not in a good state. We studied the characters of B. hayeki with a morphometric comparison to its sympatric congener B. cristatella and allopatric congener, B. jubata from Sumatra Island, Indonesia. Based on the current distribution pattern and the apparent threats, we update the conservation status of B. hayeki using IUCN Red List Criteria and propose that it be considered as an Endangered (EN) species endemic of northern Sumatra including Aceh. We also provide a key to the recognized Bronchocela species, based on examined material and literature.